Does low-cost GIC have the same survival rate as high-viscosity GIC in atraumatic restorative treatments? A RCT - Marcoeli Silva de MOURA; Geovanna Peres de SOUSA; Maria Hellen Sâmia Fortes BRITO; Mikaelle Claro Costa SILVA; Marina de Deus Moura de LIMA; Lúcia de Fátima Almeida de Deus MOURA; Renata Correa PASCOTTO; Cacilda Castelo Branco LIMA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Atraumatic Restorative Treatment (ART) is one of the strategies used to control dental caries; it involves hand instruments for removal of carious tissue, and restorations using high-viscosity Glass Ionomer Cement (GIC). The present controlled clinical trial aimed to evaluate the performance of low-cost GIC indicated for ART in primary teeth, compared with high-viscosity GIC, after one year of follow-up. Two-to six-year-old children with dentin caries lesions on one or two surfaces of anterior and posterior teeth were selected. The children were randomly assigned to 2 groups according to the restorative material used: G1 (control) - Ketac Molar®; G2 (experimental) - Vitro Molar®. Treatments were performed in a school setting, following the guidelines of the ART. A total of 728 restorations were performed in 243 children. Descriptive analysis and Poisson regression were applied, with a significance level of p < 0.05. After 12 months, 559 (76.8%) restorations were re-evaluated. The success rate was evaluated by the prevalence ratio (PR), associated with restorations performed in primary second molars (PR = 1.21; 95%CI = 1.03-1.42), and with small (PR = 1.35; 95%CI = 1.14-1.60) or medium cavities (PR = 1.29; 95%CI = 1.08-1.55), using Ketac Molar® material (PR= 1.07; 95%CI = 1.01-1.15), considering p < 0.05. Small or medium restorations in primary second molars performed with high-viscosity GIC (Ketac Molar®) were more successful than restorations performed with low-cost GIC indicated for ART.